Effect of Licorice (Glycyrrhiza glabra) Extract as an Immunostimulant on Serum and Skin Mucus Immune Parameters, Transcriptomic Responses of Immune-Related Gene, and Disease Resistance Against Yersinia ruckeri in Rainbow Trout (Oncorhynchus mykiss) - Darvishi, Mostafa; Shamsaie Mehrgan, Mehdi; Khajehrahimi, Amir Eghbal (Frontiers in Veterinary Science, 2022)
This study was designed to appraise the effect of licorice herbal supplement on the immune status of rainbow trout fingerlings. Accordingly, five diets were formulated with different levels of licorice extract including 0 (control), 0.5 g kg-1 (LE0.5), 1 g kg-1 (LE1), 2 g kg-1 (LE2), and 3 g kg-1 (LE3). The fingerlings (10.0 ± 0.1 g initial mean weight) received the diets in triplicates (30 fish in each replicate) for 56 days. The results showed the white blood cells and their differential number (lymphocytes and monocytes) were remarkably increased by LE2 supplementation (P < 0.05). The oral administration of LE2 significantly increased the levels of serum immunoglobulin (Ig), lysozyme activity, and complement components (C3 and C4) compared to others. Meanwhile, the serum bactericidal activity against Yersinia ruckeri in LE2 and LE3 treatments was significantly higher than others except for LE1 (P < 0.05). Also, serum alternative complement activity significantly improved in all treated groups except LE0.5 compared to the control group (P < 0.05). In terms of skin mucosal immunity, the fish fed with LE2 and LE3 diets exhibited notably higher lysozyme activity, alkaline phosphatase activity, and Ig value than other groups (P < 0.05). The highest skin mucus bactericidal activity against Y. ruckeri was obtained in LE2 treatment (P < 0.05). In addition, dietary LE2 significantly increased the relative expression of immune-associated genes including tumor necrosis factor-α, interleukin-1β, interleukin-8, and IgM and the former treatments showed higher values than the control group. The cumulative mortality of fish against Y. ruckeri infection was notably reduced from 53.6% in the control group to 29.0% in LE3 treatment. Overall, the dietary administration of LE at 2 g kg-1 had the best effects on immunocompetence in rainbow trout.